2009
DOI: 10.1111/j.1524-4741.2009.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Oncogenic Markers in Ductal Carcinoma In Situ of the Breast: A Clinicopathologic Study

Abstract: Ductal carcinoma in situ (DCIS) is a heterogeneous malignant condition of the breast with an excellent prognosis. Until recently mastectomy was the standard treatment. As the results of the National Surgical Adjuvant Breast and Bowel Project-17 trial and the introduction of the Van Nuys Prognostic Index (VNPI) less radical therapies are used. Objectives are to identify clinicopathologic and biologic factors that may predict outcome. Cases of DCIS diagnosed in two Belgian University Centers were included. Paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 52 publications
3
53
0
1
Order By: Relevance
“…9,10,24,28 Additionally, Kepple et al 29 and Kerlikowske et al 30 found Her-2 positivity to be significantly associated with an increased risk of recurrence in DCIS. This correlates with findings in the previous study, in which Her-2 status was inversely related to bcl-2 status, a marker of low-grade breast neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10,24,28 Additionally, Kepple et al 29 and Kerlikowske et al 30 found Her-2 positivity to be significantly associated with an increased risk of recurrence in DCIS. This correlates with findings in the previous study, in which Her-2 status was inversely related to bcl-2 status, a marker of low-grade breast neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptor (ER) and progesterone receptor (PR) were among the first markers studied in breast cancer and have been evaluated in DCIS. 9,16,17 Research on marker status in DCIS has shown hormone receptor status to be more effective as a predictor of response to treatment than as a predictor of time to recurrence. 9, 10 Balleine et al 10 established a binary molecular grading scheme for DCIS in 2008 based on nuclear grade and Ki-67 score.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is known that some women treated for DCIS subsequently develop invasive breast cancer, which is associated with a poorer prognosis. Moreover, in rare cases, DCIS may behave as an aggressive breast cancer, whereby a woman may die from metastatic disease without any evidence of invasive cancer at the time of being treated for DCIS (Altintas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, for the past 6 years we have routinely stained all of the tumors from our DCIS patients for the over-expression of HER-2. Other biologic markers that are may have prognostic significance include HER 1-4, Ki67, p21, bcl-2, p16 and COX-2, c-myc and survivin [10,13,49].…”
Section: Immunotherapy and Ductal Carcinoma In Situmentioning
confidence: 99%